PERBEDAAN EFEKTIFITAS MASSAGE PUNGGUNG DAN KOMPRES HANGAT PAYUDARA TERHADAP PENINGKATAN KELANCARAN PRODUKSI ASI DI KLINIK WIRNATA KECAMATAN MEDAN SUNGGAL - Vitrilina Hutabarat; Kristin Natalia; Stefani Anastasia Sitepu; Mutiara Dwi Yanti (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Breastfeeding is a gift given by God to women. Because breast milk is the best nutrition for babies, especially at the age of 0-6 months. With exclusive breastfeeding, mothers should get nutritious and protein foods because it will affect their milk. The purpose of this study was to determine the differences in the effectiveness of back massage and breast warm compresses to increase the smooth production of breast milk at the Wirnata Clinic, Medan Sunggal District. This study used Pre and Post Test Control Two Group Desigh, namely to determine the difference in the effectiveness of back massage and breast warm compresses before and after being given. The population in this study were 20 respondents and all of them were used as research samples. In this study using the McNemar Test. The results showed that there was a difference in the effectiveness of back massage on increasing the smoothness of breast milk production at the Wirnata Clinic, Medan Sunggal District with a p-value = 0.008 < (0.05) and warm breast compresses on increasing the smooth milk production at the Wirnata Clinic, Medan Sunggal District with a value of p-value = 0.016 < (0.05). The conclusion of this study is that there are differences in the effectiveness of back massage and warm breast compresses on increasing the smooth production of breast milk at the Wirnata Clinic, Medan Sunggal District. It is suggested to the Wirnata Clinic to be used as a reference about the benefits of back massage and warm breast compresses to increase the smooth production of breast milk.